Dėl būdvardžių su priesaga -intelis (-ė) kilmės - Ambrazas, Saulius (Baltistica, 2004)
ON THE ORIGIN OF ADJECTIVES WITH THE SUFFIX -intelis (-ė) Diminutives with the suffix -intelis (< -int- + -elis), in the 16th17th centuries characteristic not only of the West Lithuanian (as in Modern Lithuanian) but also of the East Lithuanian dialects (cf. mažiñtelis ‘very small’ DK 716; DP l0x; SD1 76; SD3 53,163, 434; SP 129918-19, 3663), are derived from archaic *-nt- nouns (cf. Lith.vien-iñt-elis and vien-ùnt-elis ‘quite alone’ wien-uñtas ‘someone’). In Indo-European they denote some kind of attributive (cf. participles and old hydronyms, e. g. Lith. Sãlantas) and diminutive meaning (cf. Lith. balt-iñt-elis and OCzech. běl-úcí ‘very white’, also Hitt. aššuwant- : aššu- ‘good’).